Penggunaan Bahasa Indonesia Dalam Dakwah Keagamaan - Ahmad Syafei; Kelvin Wahana Putra (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
The problem in this study is whether the use of rhetorical and figurative language styles in Ustad Maulana's da'wah at Islamic events is beautiful, and its implications for Indonesian learning in high school. The purpose of this study is to describe the rhetorical and figurative language style in Ustad Maulana's da'wah at Islamic events is beautiful, and its implications for Indonesian learning in high school. The method used is a qualitative descriptive method. The source of research data is the speech in Ustad Maulana's da'wah at the Islamic event was beautiful for the period 2015-2016. In this study, the data collection technique is the listen and record technique, and the sampling technique is purposive sampling (random). Based on the results of the overall analysis, the author concludes that the language style in Ustad Maulana's da'wah at the Islamic event is beautiful is a rhetorical language style including repetition, alliteration, apostrophe, asindeton, pleonasm, tautology, erothesis or rhetorical questions, prolepsis, correction, and hyperbole, then figurative language styles include equations or similes, metaphors, and allegories. The implications of language style on Indonesian language learning in high school are the learning material for grade XI students in odd semesters about analyzing content, structure, and language in lectures. Indonesian is also used in da'wah activities, both by ustadz and missionaries in Islam, as well as by evangelists in Christianity. Indonesian used to convey religious teachings and to communicate with people who do not know religion. The use of Indonesian in da'wah makes it easier for preachers to convey religious messages to the wider community. In addition, Indonesian is also used in mass media, such as television, radio, and newspapers to convey da'wah to the public.